1986
DOI: 10.1002/ange.19860980915
|View full text |Cite
|
Sign up to set email alerts
|

CC‐Kupplung von CO2 und Butadien an Eisen(o)‐Komplexen – ein neuer Weg zu α,ω‐Dicarbonsäuren

Abstract: Der C1‐Baustein CO2 läßt sich unter CC‐Verknüpfung an den Fe0‐Komplex 1, L=PMe3, addieren. Der entstehende Carboxylat‐Komplex 2 ist sehr stabil und zeigt in Lösung ein dynamisches Verhalten. 2 reagiert mit FeCl3 zur linearen, doppelt ungesättigten α,ω‐Dicarbonsäure 3.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 8 publications
0
12
0
2
Order By: Relevance
“…Hoberg et al and others [5,6,7,8] have revealed metallalactones, in particular nickelalactones ("Hoberg complexes"), [9] to be stable and isolable intermediates of the potential catalytic coupling of ethylene and CO 2 , but it has never been possible to assemble the elementary reactions of the putative catalytic cycle proposed by Walther et al, [10] nor has it been possible to actually close the catalytic cycle itself. Despite the development of a catalytic route to the structurally similar acrylamides from alkenes and isocyanates (isoelectronic to CO 2 ), [11] and an intensive search for other catalytically active metals from the nickel (Pd, Pt) [12,13] and iron triads, [14] the basic obstacles for a catalytic transformation have not been overcome; the prohibitive overall thermodynamic situation for the production of acrylic acid (DG = + + 42.7 kJ mol À1 ), [15] the limitation to a small set of ligands, the unproductively low reaction temperatures (down Keywords: C 1 building blocks · carbon dioxide fixation · carboxylation · homogeneous catalysis · nickel Abstract: For more than three decades the catalytic synthesis of acrylates from the cheap and abundantly available C 1 building block carbon dioxide and alkenes has been an unsolved problem in catalysis research, both in academia and industry. Herein, we describe a homogeneous catalyst based on nickel that permits the catalytic synthesis of the industrially highly relevant acrylate sodium acrylate from CO 2 , ethylene, and a base, as demonstrated, at this stage, by a turnover number of greater than 10 with respect to the metal.…”
Section: Introductionmentioning
confidence: 99%
“…Hoberg et al and others [5,6,7,8] have revealed metallalactones, in particular nickelalactones ("Hoberg complexes"), [9] to be stable and isolable intermediates of the potential catalytic coupling of ethylene and CO 2 , but it has never been possible to assemble the elementary reactions of the putative catalytic cycle proposed by Walther et al, [10] nor has it been possible to actually close the catalytic cycle itself. Despite the development of a catalytic route to the structurally similar acrylamides from alkenes and isocyanates (isoelectronic to CO 2 ), [11] and an intensive search for other catalytically active metals from the nickel (Pd, Pt) [12,13] and iron triads, [14] the basic obstacles for a catalytic transformation have not been overcome; the prohibitive overall thermodynamic situation for the production of acrylic acid (DG = + + 42.7 kJ mol À1 ), [15] the limitation to a small set of ligands, the unproductively low reaction temperatures (down Keywords: C 1 building blocks · carbon dioxide fixation · carboxylation · homogeneous catalysis · nickel Abstract: For more than three decades the catalytic synthesis of acrylates from the cheap and abundantly available C 1 building block carbon dioxide and alkenes has been an unsolved problem in catalysis research, both in academia and industry. Herein, we describe a homogeneous catalyst based on nickel that permits the catalytic synthesis of the industrially highly relevant acrylate sodium acrylate from CO 2 , ethylene, and a base, as demonstrated, at this stage, by a turnover number of greater than 10 with respect to the metal.…”
Section: Introductionmentioning
confidence: 99%
“…Hoberg showed that an otherwise identical mono-and bis-carboxylation could also be achieved using Fe-complexes [116]. Kinetic studies by Geyer and Schindler using isoprene as model compound highlighted the importance of the ligands employed, suggesting that future catalytic variants should be focused on ligand design [117].…”
Section: Scheme 32mentioning
confidence: 97%
“…Hoberg's studies on the Ni-mediated mono-and bis-carboxylation of butadiene [112,113] Behr and Kanne studied the behavior of trienes bearing both an isolated olefin and a conjugated 1,3-diene moiety under similar conditions, demonstrating that the carboxylation event is selective for 1,3- 26 dienes and that the isolated olefin does not affect the outcome of the reaction [114]. Hoberg showed that an otherwise identical mono-and bis-carboxylation could also be achieved using Fe-complexes [116]. Kinetic studies by Geyer and Schindler using isoprene as model compound highlighted the importance of the ligands employed, suggesting that future catalytic variants should be focused on ligand design [117].…”
Section: Scheme 32mentioning
confidence: 99%